2007
DOI: 10.1166/jnn.2007.335
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Thermostat Configurations on the Mechanical Properties of Carbon Nanotubes in Molecular Dynamics Simulations

Abstract: The effect of thermostat configurations on the mechanical behavior of empty and butane (n-C4H10) filled (10, 10) carbon nanotubes (CNTs) is examined using classical, atomistic, molecular dynamics (MD) simulations. In particular, the influence of different types of thermostats, relative numbers of thermostat atoms, and rates of deformation are considered. The compressive forces on the atoms are calculated using the second generation reactive empirical bond-order potential. The results indicate that use of a Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Researchers observed that the Nosé-Hoover and velocity rescaling thermostat results in reasonable mechanical deformation modes regardless of the percentage of thermostat atoms Heo and Sinnott 2007). In Fig.…”
Section: Thermostatmentioning
confidence: 95%
“…Researchers observed that the Nosé-Hoover and velocity rescaling thermostat results in reasonable mechanical deformation modes regardless of the percentage of thermostat atoms Heo and Sinnott 2007). In Fig.…”
Section: Thermostatmentioning
confidence: 95%
“…The revised REBO realistically describes the properties of molecular and solidstate carbon materials, including bond energy, bond lengths, and lattice constant. 15 Hitherto the REBO potential has been widely used in the analysis of CNTs 18,[22][23][24][25][26][27][28][29][30][31] and has been proved to furnish reliable results when compared to the more accurate but computationally expensive tight-binding 32,33 or ab initio DFT methods. 34,35 In the MD simulations, the fifth-order Gear's predictorcorrector integration scheme is employed with a time step size of 1 fs.…”
Section: Computational Modelmentioning
confidence: 99%
“…The environmental temperature of the simulations ͑300 or 800 K͒ is controlled by a velocity-rescaling thermostat that has been shown to have negligible effects on the mechanical behaviors of CNTs. 18,26,27 The compression of CNTs under axial loading is accomplished by prescribing small displacement increment to the top five rings of atoms along the axial direction while constraining the bottom five rings of atoms. The other atoms are allowed to move freely during a relaxation period to reach a new equilibrium state.…”
Section: Computational Modelmentioning
confidence: 99%
“…In addition, long-range van der Waals interactions are included in the form of a Lennard-Jones potential [37]. The system temperature is maintained at 300 K using a velocity-rescaling thermostat that has been shown to have negligible effects on the mechanical behavior of CNTs [39]. The particular nanotubes that are considered are (15,15) armchair and (26,0) zigzag SWCNTs.…”
Section: Methodsmentioning
confidence: 99%